ROLE OF KAOLIN ON HEMTOLOGICAL, BIOCHEMICAL AND SURVIVAL RATE OF CYPRINUS CARPIO CHALLENGED WITH PESUYDOMONAS AERUGINOSA - Abdulmotalib J. Al-Rudainy; S. A. Mustafa; A. A. Ashor; M. D. Bader (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
In present study, we assessed the role of kaolin [(Al2Si2O5(OH)4), an inert clay], for treatment of common carp, Cyprinus carpio experimentally infected with Pesudomonas aeruginosa. Fish were experimentally challenged with P. aeruginosa (LD50= 2±0.2×109 CFU/ml), in untreated water or water treated with addition of kaolin at levels of 4, 6 and 8g/l (G1, G2 and G3 respectively). Over the 5‐day course of kaolin treatment led to significantly (P ≤ 0.05) improved of survival (100%) in treated groups (G2 and G3) as compared to untreated fish (infected group; 75% survival). Considerable changes were observed in blood parameters, leucocyte count recorded significant increase (P≤0.05) in G2 and G3 relative to C- and C+ groups. Erythrocyte count, Hb content and HT(%) reported significant decrease (P≤0.05) in all treated groups (G1, G2 and G3) related to C- group. Globulin level registered significantly increased (P≤0.05) in G2 and G3 than C+ group. The current study strongly recommends that treatment of common carp infected with kaolin at 6 and 8g/l improves survival, hematological and biochemical profile, against P. aeruginosa. Future complete molecular studies are required before application of kaolin as a treatment in aquaculture.